Mode of perpetuation of Erysiphe pisi in dry temperate zone of Himachal Pradesh - H.K. CHAUDHARY, A.S. KAPOOR and (Indian Phytopathology, 2002)
Powdery mildew of peas (Pimm sativum L.), caused by Erysiphe pisi DC, is an important disease of peas and occurs every year in severe proportions in dry temperate zone of Himachal Pradesh. There are very few observations on the role of cleistothecia in the annual recurrence of E. pisi especially in tropical and sub-tropical regions. The frequent formation of cleistothecia in the dry temperate zone of Himachal Pradesh, led us to study the role of cleistothecia in the annual recurrence of E. pisi. So development of E. pisi on P. sativum, from conidial infection to cleistothecia dehiscence in 1990 and 1991 in an area 2462 m above sea level was followed systematically. A small observation plot (10 m 2) of garden pea (Lincoln) was sown on 15 May1990 and 1991 at Kukumseri. Observations on appearance of conidia and cleistothecia formation were made alongwith on 65 pea germplasm lines and pea breeding material (F4 and F5) during 1990. Similar observations were made in mid-hills, sub-humid zone of Himachal Pradesh in1991 in an area 1220 m above sea level. Sowings were made on 10 November, 1991.